BENARKAH SUMBER DAYA LANGKA?: TINJAUAN MEKANISME DISTRIBUSI DALAM PERSPEKTIF EKONOMI ISLAM - Syafaat Muhari (Fakultas Syariah dan Ekonomi Islam Institut Ilmu Al-Qur'an (IIQ) Jakarta, 2019)
Scarcity of resources has been an issue that has long been discussed by economists and policy makers. The human population increases according to the geometric progression while the amount of production especially food increases according to the arithmetic sequence. Meanwhile, in the Islamic view of scarcity, the main problem as stated in the conventional economic perspective is actually not entirely true because all human needs have been guaranteed by Allah SWT and that the natural wealth that exists in this world is sufficient to meet human needs. Humans must be able to separate what is the need (need) and also the desire (want). If humans are able to maintain and fulfill the five basic needs (dharuriyat), namely the fulfillment of the needs of religion, reason, wealth, soul and offspring, then scarcity should not occur. In addition, the scarcity is also caused by an unfair economic distribution system.